Revealing the regulation of water dipole potential to aggregation of amyloid‐β 42 at chiral interface by surface‐enhanced infrared absorption spectroscopy - Manyu Zhu; Shanshan Li; Qixin Liu; Yuqi Zhang; Zihao Li; Yiran Wang; Lie Wu; Xiue Jiang (Aggregate)
Abstract Surface chirality plays an important role in determining the biological effect, but the molecular nature beyond stereoselectivity is still unknown. Herein, through surface‐enhanced infrared absorption spectroscopy, electrochemistry, and theoretical simulations, we found diasteromeric monolayers induced by assembled density on chiral gold nanofilm and identified the positive contribution of water dipole potential at chiral interface and their different interfacial interactions, which result in a difference both in the positive dipoles of interfacial water compensating the negative surface potential of the SAM and in the hindrance effect of interface dehydration, thereby regulating the interaction between amyloid‐β peptide (Aβ) and N‐isobutyryl‐cysteine (NIBC). Water on L‐NIBC interface which shows stronger positive dipole potential weakens the negative surface potential, but its local weak binding to the isopropyl group facilitates hydrophobic interaction between Aβ42 and L‐NIBC and resulted fiber aggregate. Conversely, electrostatic interaction between Aβ42 and D‐NIBC induces spherical oligomer. These findings provide new insight into molecular nature of chirality‐regulated biological effect.